2003
DOI: 10.1001/archpedi.157.12.1184
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Disease at the Age of 7 Years After Pertussis Vaccination in Infancy

Abstract: Pertussis vaccination in infancy with any of these vaccines was not associated with allergic manifestations at the age of 7 years, apart from a higher prevalence of positive skin prick test results after an experimental 2-component vaccine, which is no longer in use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 29 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…The studies conducted that way yielded inconsistent results. Our results are consistent with the observations of other authors who did not confirm the influence of DTwP exposure on the development of allergy [ 11 , 15 , 16 ]. Some of them even observed the protective effect of DTwP vaccination with respect to the onset of asthma and other allergic diseases in later life [ 17 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The studies conducted that way yielded inconsistent results. Our results are consistent with the observations of other authors who did not confirm the influence of DTwP exposure on the development of allergy [ 11 , 15 , 16 ]. Some of them even observed the protective effect of DTwP vaccination with respect to the onset of asthma and other allergic diseases in later life [ 17 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…Hence, unvaccinated children are a highly selected and usually atypical group. It is related to studies on DTwP as well [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A reported sequela of Bordetella spp. infections is the increased risk for asthma and allergies [ 84 , 85 , 86 ], which suggests that bacteria trigger this hyper-reactive eosinophilic state. However, recent literature has revealed that B. bronchiseptica can suppress eosinophil influx in the lungs to promote bacterial persistence [ 87 ], suggesting that eosinophils, in fact, actively participate in the immune responses to Bordetella spp.…”
Section: Eosinophils and Innate Immunitymentioning
confidence: 99%
“…Atopic disease usually develops in the early life of children, whose immune system is under development [9]. ere is evidence revealing the relationship between vaccination and the risk of atopic disease [10], and many publications have investigated this hypothesis [11][12][13][14][15]. Among those relationships, the most investigated one is the relationship between BCG vaccine and atopic disease, but the results remain controversial.…”
Section: Introductionmentioning
confidence: 99%